2021
DOI: 10.3389/fmicb.2021.682111
|View full text |Cite
|
Sign up to set email alerts
|

What’s a Biofilm?—How the Choice of the Biofilm Model Impacts the Protein Inventory of Clostridioides difficile

Abstract: The anaerobic pathogen Clostridioides difficile is perfectly equipped to survive and persist inside the mammalian intestine. When facing unfavorable conditions C. difficile is able to form highly resistant endospores. Likewise, biofilms are currently discussed as form of persistence. Here a comprehensive proteomics approach was applied to investigate the molecular processes of C. difficile strain 630Δerm underlying biofilm formation. The comparison of the proteome from two different forms of biofilm-like growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 170 publications
1
16
0
Order By: Relevance
“…All of these results are consistent with transcriptional data performed during biofilm formation which show that the genes encoding the flagella components are less expressed, while those of the T4P are more expressed [184,185,192]. Moreover, a recent systematic proteomics study showed that flagella and pili proteins were more abundant in biofilm formed in liquid cultures than in biofilm formed on agar [189]. This confirms that pili and flagella are expressed and produced under biofilm forming conditions but are dependent on the model and conditions used.…”
Section: Surface Structures and Their Importance In Biofilm Formationsupporting
confidence: 89%
See 4 more Smart Citations
“…All of these results are consistent with transcriptional data performed during biofilm formation which show that the genes encoding the flagella components are less expressed, while those of the T4P are more expressed [184,185,192]. Moreover, a recent systematic proteomics study showed that flagella and pili proteins were more abundant in biofilm formed in liquid cultures than in biofilm formed on agar [189]. This confirms that pili and flagella are expressed and produced under biofilm forming conditions but are dependent on the model and conditions used.…”
Section: Surface Structures and Their Importance In Biofilm Formationsupporting
confidence: 89%
“…Several regulation pathways and cascades are involved in C. difficile biofilm formation, and those involved vary according to the growth conditions. Every study using biofilms from liquid cultures has identified the transcriptional regulators CcpA, CodY, Spo0A and SigL/RpoN as key transcriptional factors involved in biofilm formation [184,185,189,192,219]. CcpA, CodY and SigL/RpoN are global regulators of the metabolism and support the idea that biofilm formation is dependent on a metabolic shift in planktonic cells.…”
Section: Regulation Of Biofilm Formationmentioning
confidence: 84%
See 3 more Smart Citations